Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/adhm.202302907
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of an Artery‐on‐a‐Chip to Unravel Novel Regulators and Therapeutic Targets in Vascular Diseases

Valentina Paloschi,
Jessica Pauli,
Greg Winski
et al.

Abstract: In this study, organ‐on‐chip technology is used to develop an in vitro model of medium‐to‐large size arteries, the artery‐on‐a‐chip (AoC), with the objective to recapitulate the structure of the arterial wall and the relevant hemodynamic forces affecting luminal cells. AoCs exposed either to in vivo‐like shear stress values or kept in static conditions are assessed to generate a panel of novel genes modulated by shear stress. Considering the crucial role played by shear stress alterations in carotid arteries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…We determined the expression of CB1 in human and mouse atherosclerotic vessels at the mRNA level due to the lack of specific antibodies to detect CB1 at the protein level. 34 In human plaque single cell RNA sequencing data from the Munich Vascular Biobank, 18 we detected CNR1 only in ECs, probably because the sensitivity of analysis was insufficient to detect CNR1 expressed by other plaque cell types. Remarkably, we found that endothelial CB1 expression is regulated by shear stress, revealing an increased receptor expression in atheroprone regions of mouse aortas and in HAoECs subjected to OSS.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We determined the expression of CB1 in human and mouse atherosclerotic vessels at the mRNA level due to the lack of specific antibodies to detect CB1 at the protein level. 34 In human plaque single cell RNA sequencing data from the Munich Vascular Biobank, 18 we detected CNR1 only in ECs, probably because the sensitivity of analysis was insufficient to detect CNR1 expressed by other plaque cell types. Remarkably, we found that endothelial CB1 expression is regulated by shear stress, revealing an increased receptor expression in atheroprone regions of mouse aortas and in HAoECs subjected to OSS.…”
Section: Discussionmentioning
confidence: 93%
“…While CB1 expression has been reported in human plaques, 17 the specific cell types contributing to CB1 signaling within the plaque have not been well characterized. Therefore, we screened single-cell RNA sequencing data from human carotid plaques 18 and found that the CB1-encoding gene CNR1 was detectable in plaque endothelial cells (Figure 1A-B). CNR1 expression was not detectable in other cell clusters of human atherosclerotic plaques identified by single cell RNA sequencing, although the expression has previously been demonstrated in a variety of immune cells 19 and more recently in murine plaque macrophages by in situ hybridization.…”
Section: Resultsmentioning
confidence: 99%